Characterisation of red palm oil microcapsule with solution-enhanced dispersion by supercritical carbon dioxide technology - Lee, Wan Jun (2018)
The carotenes and vitamin E (vE) in red palm oil (RPO) are highly susceptible to degradation which limits the utilisation of RPO as functional ingredient. The objective of this research was to enhance the stability of RPO and to slow down the degradation of bioactive compounds by microencapsulation using the solution-enhanced dispersion by supercritical carbon dioxide (SEDS) technology without the aid of organic solvents. This study began with the determination of RPO solubility and the concentration of carotenes, tocopherols and tocotrienols from the solubilised RPO in supercritical carbon dioxide (scCO2) using the dynamic flow-through method, at different pressures (8.5– 25.0 MPa) and temperatures (40– 60°C), at a pre-determined scCO2 flow rate of 2.9 g/min. The RPO had solubility of 0.5– 11.3 mg/g CO2 and was significantly affected by pressure and temperature. The β-carotene recorded higher concentration in scCO2 (3 x 10-3 μmol/mol to 17 x 10-3 μmol/mol) compared to α-carotene (2 x 10-3 μmol/mol to 15 x 10-3 μmol/mol); and tocotrienols were more soluble (0.4 μmol/mol to 26 μmol/mol) than tocopherols (5 x 10-2 μmol/mol to 3 μmol/mol) following the preference of γ-T3 > δ-T3 > α-T3 > α-T> β-T > γ-T > δ-T. Adachi-Lu model was the best fitting model for the solubility of RPO and the concentration of bioactive compounds in scCO2. The RPO was then microencapsulated with SEDS at 10.0– 15.0 MPa, 40– 60°C, and feed injection flow rate 2.5 mL/min. The microcapsules were characterised in terms of their physical, structural, and thermal properties and also their oxidative stability. Microcapsules with microencapsulation efficiencies (ME) of oil (64– 92%), retention efficiencies (RE) of carotenes (50– 82%), RE of vE (64– 94%), particle size (4– 9 μm) were obtained. Comparing to the SEDS microcapsules (SEDSM), the spray dried microcapsules (SD-M) as the control had wrinkled surfaces with lower ME (79%), similar RE (carotene= 85%, vE= 93%), larger particle size (17 μm) and larger particle size distribution. The fatty acid composition, chemical structures and thermal properties of the oil were not altered by the SEDS process. The thermal stability, oxidative stability and retention of carotenes and vE of RPO were improved after SEDS encapsulation. Colour change and degradation in carotenes and vE concentration for microcapsules and bulk oil at different storage temperatures (25°C, 45°C, 65°C, and 85°C) for up to 28 weeks was investigated and the degradation kinetics using rate law and Arrhenius equation were studied. The degradation of carotenes and vE was well fitted into the first-order kinetic model. A negative correlation was found with the change in colour parameters to the degradation of carotenes, and two equations to correlate the relationship were established, recording R2 of 0.8152 for SEDS-M and 0.8283 for SD-M. In summary, the SEDS process was able to produce RPO microcapsules containing high concentration of carotenes and vE, high oil encapsulation efficiency whilst able to provide protection against the deterioration of the bioactive components and oil quality.